Procambarus (Ortmannicus) luxus (Decapoda: Cambaridae), a new crayfish from southern Texas - Johnson, Daniel P. (Zootaxa, 2011)
Procambarus (Ortmannicus) luxus is described from Bee, Brooks, Jim Wells, Kleberg, Nueces, Refugio and San Patricio counties, Texas. It may be distinguished from its nearest relative, P. (O.) texanus, by its strongly asymmetrical first pleopods with proximal extremities separated by a distinct gap; strongly corneous, narrow, scarcely laterally deflected mesial process; slightly more recurved cephalic process and central projection; and an annulus ventralis which is more weakly overhung by the adjacent sternum and bears a prominent caudomedian tonguelike projection.